Analisis Beban Kerja Pada Bagian Tata Usaha Puskesmas Probolinggo Menggunakan Metode WLA - Arisandi Dwi Gustian; Tismawati Tismawati; Haryono Haryono (Energy - Jurnal Ilmiah Ilmu-Ilmu Teknik, 2022)
Working load at administration office of public health center seem to be able to be obtimised because it is obviously some of the officers still have leasure time and some does not, other does not start work on time and ended early. It is seem that overload works occur in any division occur but it may because that they can not manage the time schedule. By using working load analysis it can be justified that they are able to work properly or not. From the analysis it is known that some officer has overload work and some has not.